COMPARATIVE CHARACTERISTIC OF TRICHOTHECENE MYCOTOXIN COMPLEX OF FUSARIUM POAE (PECK) WOLLENW. THE STRAINS FROM DIFFERENT TROPHIC GROUPS - I. М. Курченко; К. С. Циганенко (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2013)
Aim. The main goal of our investigation was a comparative study of the ability to synthesize trichothecene toxins by 15 strains of Fusarium poae from different trophic groups: 5 soil strains, 5 plant pathogenic and 5 endophytic strains. Methods. The standard methods of isolation and identification of mycotoxins were used. Results. It was established that T-2 toxin was detected for 4 soil strains, 3 plant pathogenic and 2 endophytic strains. It was shown that its content was maximal for soil strains and reached 188.8±32.2 μg/l, was lower for plant pathogenic ones and the lowest for endophytic strains. The content of HT-2 toxin and T-2 tetraol was higher for soil strains than plant pathogenic and endophytic ones, and T-2 triol – higher for plant pathogens than soil strains. T-2 triol was observed only for one endophytic strain. Neosolaniol is produced by 3 soil and 2 plant pathogenic strains, but not synthesized by endophytes. Conclusions. Thus, it was established that endophytes F. poae produce significantly less trichothecene mycotoxins than the strains of this species from other trophic groups. This physiological peculiarity allows them apparently to be in a mutualism with the plants.